Characterisation and analytical modelling of GaN HEMT‐based varactor diodes. Issue 23 (1st November 2015) - Hamdoun, A.; Roy, L.; Himdi, M.; Lafond, O.
Abstract : Varactor diodes fabricated in 0.5 and 0.15 µm GaN HEMT (high‐electron‐mobility transistor) processes are modelled. The devices were characterised via DC and RF small‐signal measurements up to 20 GHz, and fitted to a simple physical equivalent circuit. Approximate analytical expressions containing empirical coefficients are introduced for the voltage dependency of capacitance and series resistance. The analytical solutions agree remarkably well with the experimentally extracted C–V curves and can be used as a general model to represent the nonlinear behaviour of GaN‐based varactors devices.